CP/M: A FAMILY OF 8- AND 16-BIT COMPUTER OPERATING SYSTEMS. - Kildall, Gary (Education)
This is the story of the development of the computer CP/M and MP/M operating system by Gary Kildall of Digital Research Company. PL/M is described as the basis for CP/M, and MP/M is the multiprogramming for the microprocessor. The author discusses the adaptation of these operating systems to the newly emerging 16 and even the 32 bit machines.